The INFLUENCE OF REVENUE, OPERATIONAL COSTS, GROSS MARGIN, PROFITABILITY, DEBT TO EQUITY RATIO (DER) ON CORPORATE INCOME TAX EXPENSES IN COAL MINING COMPANIES LISTED ON THE BEI ​​FOR THE 2019 - 2022 PERIOD - Tahir, Febryansyah; Cusyana, Silvi Reni Cusyana; Nurwati, Nurwati (Jurnal Manajemen & Bisnis Jayakarta, 2024)
The international world in recent months has been shocked by a pandemic, namely an outbreak of a disease caused by a virus called corona or better known as Corona Virus Diseases-19 (Covid-19). The sector that was also affected by the outbreak of the pandemic in 2020 was the mining sector, one of which was coal mining. Sales volume is closely related to controlling operational costs, because operational costs show how the company generates its sales volume. Operating costs are a number of costs that must be incurred by a company to support the operations or activities carried out by the company. Gross profit margin is a ratio used to measure the amount of gross profit percentage on net sales. Profitability ratio is a ratio used to measure a company's ability to generate profits from its business activities. Good performance is aimed at generating maximum profits for the company through successful management. Debt to equity ratio is a type of leverage ratio. Debt to equity ratio is a ratio used to find out how much part of each rupiah of capital is used as debt collateral. In calculating income tax, profit is an important component that determines the size and size of the income tax burden. The tax rate is used as multiplication by taxable profit. The method used is quantitative descriptive. The object of this study is a Coal Mining Company listed on the Indonesia Stock Exchange with 11 companies with the technical analysis used is multiple linear regression using the F test and the t test. The variables used in this study are the variables bound by Corporate Income Tax Burden (Y), the independent variables are Revenue (X1), Operating Costs (X2), Gross Margin (X3), Profitability (X4) and Debt to Equity Ratio (X5). The results of the study show that both simultaneously and partially the independent variables are Revenue, Operating Costs, Gross Margin, Profitability and Debt to Equity Ratio have an influence and significantly on the Corporate Income Tax Burden.